Determination of Propionylbrassinolide and Its Impurities by High-Performance Liquid Chromatography with Evaporative Light Scattering Detection - Lidong Cao; Hong Zhang; Hongjun Zhang; Li Yang; Miaomiao Wu; Puguo Zhou; Qiliang Huang (Molecules, 2018)
The discovery of brassinolide in 1979, a milestone in brassinosteroids research, has sparked great interest of brassinolide analogs (BLs) in agricultural applications. Among these BLs, propionylbrassinolide has captured considerable attention because it shows plant growth regulating activity with an excellent durability. Two impurities of propionylbrassinolide were isolated and purified by semi-preparative high-performance liquid chromatography (HPLC), and the chemical structures were confirmed. For simultaneous separation and determination of propionylbrassinolide and impurities, an efficient analytical method based on HPLC with evaporative light scattering detector (HPLC-ELSD) was developed. The optimized analysis was performed on a C18 reversed phase column (250 mm × 4.60 mm, 5 μm) with isocratic elution of acetonitrile and water (90:10, v/v) as the mobile phase. The drift tube temperature of the ELSD system was set to 50 °C and the auxiliary gas pressure was 150 kPa. The regression equations demonstrated a good linear relationship (R2 = 0.9989–0.9999) within the test ranges. The limits of detection (LODs) and quantification (LOQs) for propionylbrassinolide, impurity 1 and 2 were 1.3, 1.2, 1,3 and 4.3, 4.0, 4.2 mg/L, respectively. The fully validated HPLC-ELSD method was readily applied to quantify the active ingredient and impurities in propionylbrassinolide technical concentrate. Moreover, the optimized separation conditions with ELSD have been successfully transferred to mass spectrometry (MS) detector for LC-MS determination.